Dyspepsia and Gut Microbiota in Female Patients with Postcholecystectomy Syndrome - Georgescu D; Caraba A; Ionita I; Lascu A; Hut EF; Dragan S; Ancusa OE; Suceava I; Lighezan D (Dove Medical Press, 2022)
Doina Georgescu,1,* Alexandru Caraba,1,* Ioana Ionita,1 Ana Lascu,2 Emil Florin Hut,3 Simona Dragan,4 Oana Elena Ancusa,1 Ioana Suceava,1 Daniel Lighezan1 1Department of Internal Medicine I, “Victor Babes” University of Medicine and Pharmacy, Timisoara, Romania; 2Department of Functional Sciences, Discipline of Pathophysiology, “Victor Babes” University of Medicine and Pharmacy, Timisoara, Romania; 3Department IX of Surgery I/Compartment of Hepato-Bilio-Pancreatic Surgery, “Victor Babes” University of Medicine and Pharmacy, Timisoara, Romania; 4Department of Cardiology, “Victor Babes” University of Medicine and Pharmacy, Timisoara, Romania*These authors contributed equally to this workCorrespondence: Alexandru CarabaDepartment of Internal Medicine I, “Victor Babes” University of Medicine and Pharmacy, Timisoara, Piata Eftimie Murgu 2, 300041, RomaniaTel +40 744 769 850, Fax +40 256 490 626, Email caraba.alexandru@umft.roBackground: Gallstone disease (GSD) represents one of the most frequent digestive disorders, highly reported in female gender. The purpose of the study was to explore the clinical and gut microbiota particularities of female patients with postcholecystectomy syndrome (PCS) and the possible relationship between gut dysbiosis (DB) and abdominal complaints.Patients and Methods: In total, 129 female participants: 104 outpatients divided into two equal groups, 52 PCS (+), 52 PCS (−) and 25 healthy controls were consecutively enrolled in this observational study. Patients underwent clinical examination with assessment of pain, bloating, transit disturbances, abdominal ultrasound/computer tomography/magnetic resonance imaging/endoscopic retrograde cholangiopancreatography, upper and lower digestive endoscopies. Laboratory work-ups and stool microbiology assessments were performed for all study participants (patients and controls). Stool microorganisms were identified by matrix-assisted laser desorption ionization – time-of-flight– mass spectrometry and in patients with DB also by next-generation sequencing.Results: Older age, complicated gallstones disease, associated conditions like diabetes mellitus/impaired glucose tolerance and irritable bowel syndrome were significantly present in PCS (+) group, as well as sedentary lifestyle and diets characterized by a low fiber intake (p< 0.0001). PCS (+) patients displayed significant differences related to the incidence and severity of overall gut microbiota DB, decreased H index of biodiversity and the unbalanced Firmicutes/Bacteroidetes (F/B) ratios by comparison to the PCS (−) group (p< 0.0001). Strong positive correlations of the severity of overall DB with bloating and the intestinal habit disorders, as well as of F/B ratios to all abdominal symptoms were noted.Conclusion: PCS in female patients was associated with older age, sedentary lifestyle, specific dietary habits, history of complicated gallstone disease, diabetes mellitus/impaired glucose tolerance and irritable bowel syndrome, as well as gut microbiota particularities. Overall DB and unbalanced F/B ratios were strongly correlated to abdominal complaints.Keywords: postcholecystectomy syndrome, female patients, gut microbiota imbalance